Epidemiology of Hand Injuries in a Tertiary Care Center - Bajracharya, Suraj; Shrestha, S (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: This retrospective review was performed to identify the incidence, causes, and details of hand injuries in patients presenting to a tertiary hospital of Kathmandu. MATERIAL & METHODS: Records of all patients who had sustained hand injuries for last 5 years were collected from the Medical Record section. 832 injuries of the hand in 484 patients were reported in this review. These patients were reviewed for a geat the time of injury, gender, location of the incident, mechanism of injury, and fracture specifics. RESULTS: Majority (85.5%) of patients were males with a mean age of 28.79±12.81years and the rest were females with a mean age- of 30.43 ±17.13 yrs. Machinery injuries (25.2%) were the most common cause of injuries followed by road traffic accidents (14.5%). Metacarpal bone fractures (34.6%) were the common estinjuries of the hand. Most of the patients were treated with open reduction and fixation with Kwires. CONCLUSION: The study revealed the aetio-epidemiological and clinical profile of hand injuries, and its burden in eastern Nepal. Journal of Universal College of Medical Sciences, Vol. 5, No. 2, 2017, Page: 35-39